An ecological outline of a moulting area of Teal, Vejlerne, Denmark - Kortegaard, Leo (Wildfowl, 1974)
Some of the features which are typical of the moulting area can be summarized briefly as the topography, water level (20-60 cm), shelter from prevailing winds, water temperature (16-18C), food (rich plant and animal life), clumps and small islands as refuges, and occasional patches of standing vegetation in water, which offer shelter and a means of escape. These factors are presumably important in the habitat selection by the birds ('proximate factors', cf. Hildn, 1965). In addition, the relationship to predators (including man), social factors, past tradition (moulting migration) and internal factors (timidity and physiological stress) apparently also play a part in the habitat selection, but these factors have not been investigated. From the experience gained in this study, a description of a moulting area of dabbling ducks should cover the following points. (a) Latitude and longitude; country; surface area; legal status; numbers and species of duck concerned; period of moulting. (b) Measurements of water level, air and water temperature, chloride content, and other water qualities. (c) Description of the topography and vegetation of the moulting area, including species composition and relative occurrence of species. (d) Collection of invertebrate samples from typical plant communities during the moulting period. (e) Collection of duck stomach contents for comparison with points (c) and (d). These should be obtained immediately after the ducks have fed, and be preserved at once in 4% formalin (Harrison, 1960). (f) Description of other conditions which affect the flightless birds or their habitat. It is hoped that this article will stimulate the investigation of moulting areas of Teal and other dabbling ducks in other localities. In this way, a fair impression can be gained of the general and specific requirements of these birds for their moulting areas. Such knowledge is necessary for the conservation and management of the moulting areas of duck.